Studi Penerapan Green Accounting dan Pengungkapan Sustainability Reporting Terhadap Profitabilitas - Nada Rosyidah Sari; Endah Tri Wahyuningtyas Endah Tri Wahyuningtyas (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
This study aims to investigate the implementation of green accounting and sustainability report disclosure on company profitability. The sample used in this research is green industry award-winning companies that are listed on the Indonesian stock exchange and have published a reliability report in 2012-2018. The data in this study uses secondary data, which is taken from financial reports and sustainability reports in 2012-2018. The analytical tool used to test the hypothesis is multiple regression analysis using Minitab 18. The results of this study indicate that Green Accounting and Economic Performance Disclosures have a positive and significant relation, while Environmental Performance Disclosure has no relation on profitability, and Social Performance Disclosures have a negative and significant relation on the profitability of companies that have won green industry awards listed on the Indonesian stock exchange.